Fabrication of mixed matric membrane incorporated with modified silica nanoparticles for bisphenol a removal - Salim, Mohd. Razman (Penerbit UTM Press, 2015)
The introduction of inorganic nanoparticles in polymeric dope solution for the fabrication process of membrane can potentially enhance the separation performances of membrane without negatively affecting its permeability. In this study, hollow fiber mixed matrix membranes were prepared by incorporating polyethersulfone (PES) membranes with silicon dioxide (SiO2) nanoparticles at different concentration. Prior to separation tests, the prepared membranes were characterized by SEM, EDX, DSC, water contact angle, and FTIR-ATR in order to study the impact of silica nanoparticles on the properties of the membranes. Bisphenol A (BPA) was selected as the subject compound of this study because it is one of the emerging pollutants that have been frequently detected in the water treatment plant (WTP). BPA was spike into the pre-treated water sample taken from the WTP and was used as the feed solution to evaluate the membrane performance in terms of water flux and removal rate. The addition of SiO2 was reported to improve the hydrophilicity of membrane and induce greater micro-voids formation in the membrane structures, leading to increased water flux during BPA filtration process. The presence of more silanol (Si-OH) and siloxane (Si-O-Si) bonding groups resulted from increased SiO2 contents in membrane has improved membrane adsorption rate and further increased BPA removal